The Relationship between Lifestyle and Environmental Behavior of Citizens of Shiraz City - Farnaz Dastras; Bijan Khajenoori (توسعه اجتماعی)
The aim of this study is the relationship between lifestyle and environmental behavior of citizens of Shiraz. The "lifestyle theory" of Bourdieu have used in this study related to types of lifestyle using the cocepts such as habitus, sphere and different types of capital; and also environmental behavior have selected as a set of behavior in relation to environment that have affected by individual`s position in social space. The environmental behavior of Kollmuss and Agyeman have used to operate the dimensions of environmental behavior. The survey method is used for this study and statistical population of this study included the people who are over 15 years old in 11 zones of Shiraz According to Cochran formula, the Sample size included 384 people. Statistical samples have obtained through random cluster sampling and the data of this survey have collected through the questionnaire; Ten factors were considered in related to lifestyles through factor analysis; These factors include: management body, cultural lifestyle, sporty lifestyle, leisure lifestyle, religious lifestyle, consciousness and tolerance lifestyle, politely lifestyle, internet lifestyle, high-risk diet, domestic lifestyle and healthy lifestyle. The study shows that, the main effective factors on environmental behavior are: religious lifestyle, healthy lifestyle, sporty lifestyle, leisure lifestyle and politely lifestyle. These lifestyles have a positive and powerful relationship with environmental behavior (the dependent variable) and these independent lifestyle variables, high-risk diet and internet lifestyle; have a negative and powerful relationship with environmental behavior.